The future of innovation and technology in education : policies and practices for teaching and learning excellence - Visvizi, Anna, 1976-; Lytras, Miltiadis D., 1973-; Daniela, Linda, 1967- (Emerald Publishing Limited, 2018)
This book explores the effective use of information and communication technology (ICT) in teaching and learning. Concept-laden and practice-driven discussions offer insights into the art and practice of employing virtual and augmented reality (VR/AR), electronic devices, social networks and massive open online courses (MOOCs) in education.
Prelims -- Introduction the future of innovation and technology in education: a case for restoring the role of the teacher as a mentor -- Part I: Learning innovation for digital economy and sustainable development -- Chapter 1 How to predict the unpredictable: technology-enhanced learning and learning innovations in higher education -- Chapter 2 Focus on the agency of learners to innovate in pedagogy -- Chapter 3 A review of educational innovation from a knowledge-building pedagogy perspective -- Chapter 4 Agile digital skills examination for the digital economy: knowledge and social capital management frameworks through social networking -- Chapter 5 Innovation in higher education: towards enhancing sustainable development -- Part II: The use of ICT for teaching, learning and assessment -- Chapter 6 Collaborative writing and knowledge creation in a social media online community -- Chapter 7 How to use ICT in the classroom effectively: the technological blend -- Chapter 8 The use of tablets in lower secondary education: students' perspectives and experiences -- Chapter 9 School website as a media: practice and potential of the school website content -- Chapter 10 Using Facebook as a massive open online course environment: supported functionalities and challenges -- Chapter 11 Assessing the impact of virtual reality on engineering students' spatial ability -- Chapter 12 Immersive experiences in online higher education: virtual presence and flow -- Chapter 13 Educational data mining for peer assessment in communities of learners -- Part III: Case studies -- Chapter 14 Student-teachers' ability to implement competency approach: the case of the University of Latvia -- Chapter 15 Online-to-offline teaching reform in China: outcomes-based education -- Chapter 16 A prescriptive instructional systems design model: a Rasch-model case for Saudi Arabia -- Chapter 17 Do we all speak the same language in Europe? Finding out by playing -- Chapter 18 Innovation in a Dean's office: the case of Polish HEIs -- Chapter 19 Education, innovation and the prospect of sustainable growth and development -- Index.
Includes index.
Print version record
Keywords: Educational innovations; Educational technology; Education -- Teaching Methods & Materials -- General; Educational strategies & policy